2013
DOI: 10.1590/0104-1169.3059.2363
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity, vulnerability and prevention of STD/HIV/AIDS among male adolescents: social representations in a land reform settlement

Abstract: OBJECTIVE: to analyze the relationship of masculinity, vulnerability and prevention of STD / HIV / AIDS among adolescent males of a land reform settlement in central Brazil. METHOD: a qualitative study using as precepts the strands of social representations with teenagers between 12 to 24 years. RESULTS: three categories emerged - Perception of vulnerability; Gender and vulnerability; and, Prevention and vulnerability to STD / HIV / AIDS. Adolescents felt invulnerable to sexually transmitted diseases anchored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 15 publications
2
11
0
17
Order By: Relevance
“…In addition, it was observed that there is an increase in sexual relations and a gradual cessation of condom use over the course of the relationships, suggesting that the concern with STD is restricted to the beginning of the relationship, reducing significantly as familiarity with the partner increases, which has also been found in other studies (Arraes et al, 2013;Garcia & Souza, 2010;Oliveira et al, 2009;Oltramari & Camargo, 2010). In this regard, there is a minimum time period considered necessary for the knowledge of the partner and the establishment of a relationship of trust, in which condoms may be dispensed with in favor of the contraceptive pill.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition, it was observed that there is an increase in sexual relations and a gradual cessation of condom use over the course of the relationships, suggesting that the concern with STD is restricted to the beginning of the relationship, reducing significantly as familiarity with the partner increases, which has also been found in other studies (Arraes et al, 2013;Garcia & Souza, 2010;Oliveira et al, 2009;Oltramari & Camargo, 2010). In this regard, there is a minimum time period considered necessary for the knowledge of the partner and the establishment of a relationship of trust, in which condoms may be dispensed with in favor of the contraceptive pill.…”
Section: Discussionsupporting
confidence: 78%
“…The feeling of invulnerability among adolescents has also been identified in other studies (Arraes et al, 2013;Bralock & Koniak-Griffin, 2009;Sychareun et al, 2013). The male adolescents evaluated that they had a higher chance of being infected in the future, probably due to their greater involvement in casual relationships in comparison with the female adolescents.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Entre esses fatores, destacam-se o acesso à educação e aos serviços de saúde, principalmente aqueles relacionados ao aconselhamento e testagem sorológica rápida da doença, sendo, portanto, alvos importantes para as políticas públicas de saúde. 3,4,8,15,16 De modo geral, nas últimas dé-cadas têm se destacado o maior acesso da população ao diagnóstico da doença, com a ampliação dos Centros de Aconselhamento e Testagens para as Doenças Sexualmente Tabela 2. Coeficiente de incidência de aids (por 100.000 hab.…”
Section: Discussionunclassified
“…5,6 Nos últimos trinta anos, o perfil epidemiológico da aids em várias regiões do mundo vem apresentando mudanças, por exemplo a elevação do número de casos entre mulheres, jovens e pessoas com menor grau de escolaridade, além de heterossexualização e interiorização da epidemia. 3,4,7,8 Não obstante essas alterações, a OMS relata uma redução do número de casos em âmbito mundial.…”
Section: Introductionunclassified